carcass wrote:

GyanOne wrote:

x/(x+y) = 6

=> (x+y-y)/(x+y) = 6

=> 1 - y/(x+y) = 6

=> y/(x+y) = -5

Option A

I do not understand this passage

x/(x+y) = 6 //this statement is already given in the question

=>

(x+y-y)/(x+y) = 6 // this statement adds and subtracts y from the numerator so that we get the form y/(x+y) on one side

=> 1 - y/(x+y) = 6 // this step groups ((x+y)/(x+y) -y/(x+y))

=> y/(x+y) = -5

_________________

Thanks

Kris

Instructor at Aspire4GMAT

Visit us at http://www.aspire4gmat.com

Post your queries

Join our free GMAT course

New blog: How to get that 700+

New blog: Data Sufficiency Tricks

Press Kudos if this helps!